From functional foods to immunotherapeutic agents: mechanistic insights into medicinal mushroom bioactives in chronic inflammation management - Xiaoying, Ma; Peng, Zhang; Hong, Wang; Na, Gong; Jun, Xiao; Ying, Zhao; Xun, Chen; Guoli, Liu (Frontiers in Nutrition, 2025)
BackgroundChronic inflammation underlies numerous complex diseases, yet current therapeutic strategies show limited efficacy and safety profiles. Despite extensive preclinical evidence, the mechanistic understanding and clinical translation of medicinal mushroom bioactives remain inadequately characterized.ObjectiveThis review systematically evaluates the immunoregulatory mechanisms of mushroom-derived bioactive compounds and establishes a comprehensive framework for their therapeutic application in chronic inflammatory diseases.MethodsWe analyzed mechanistic evidence for four major compound classes: polysaccharides (β-glucans), triterpenoids, phenolic compounds, and bioactive peptides, examining their effects on immune cell populations and signaling pathways.ResultsThese bioactives demonstrate multi-target anti-inflammatory activity by modulating key cellular mediators (macrophages, regulatory T cells, natural killer cells) and critical signaling cascades (NF-κB, MAPK, NLRP3 inflammasome, Nrf2/HO-1). Novel therapeutic targets including gasdermin-mediated pyroptosis provide additional intervention opportunities. However, clinical translation faces significant challenges: poor bioavailability, lack of standardization, and undefined dose–response relationships.ConclusionAdvanced delivery systems (nanoformulations, structural optimization) and precision nutrition approaches through personalized immune profiling offer promising solutions to overcome translational barriers. This analysis provides evidence-based rationale for advancing medicinal mushrooms from traditional functional foods to standardized immunotherapeutic agents for chronic inflammation management.